Effectiveness of Foreign Philanthropy Campaign and Relation with Inner Interactions in Transnational Co-Operative Organization - Lo, Wei; Huang, Sophia; Hu, Jersan (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2020)
It is of necessity for developed economic societiesto provide philanthropic services to the societies of neighboring countries. Developed societies have resource and capacity advantages in terms of knowledge technology and organizational strength; thus, it is imperative that they provide adequate supports to the comparatively more vulnerable societies. However, due to insufficient in-depth understanding to the local socio-economic structure, work mentality and value, technology capacities, and resource condition of the local societies (or social groups), the philanthropic target and local social value often come into cognitive conflicts in the process of collaboration which ultimately affect the bilateral resource integration and effectiveness of application. The study, based on the researchers’ venture in the household water purification project in rural Vietnam villages, employed action research method to confirm the cognitive gap on philanthropy, the expectation deviation on work mission, and the action deviation effect of the organizational cultures on transforming philanthropic service into philanthropic entrepreneurship encountered in the process of executing the philanthropic projects by transnational cooperative teams in the two-year overseas services.Keywords: social enterprise, social entrepreneurship, social resource, transnational philanthropic campaign